The flexibility of Islamic law in the Ganjur tradition in Lamongan, Indonesia - khoiroh, Muflikhatul; Syakur, Abd Syakur (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2023)
This article demonstrates the flexibility of Islamic family law in the Ganjur tradition in Lamongan, Indonesia, considered unique for allowing women to propose to men. Despite its uniqueness, the Ganjur tradition carries important moral teachings in the context of realizing humanistic and egalitarian family relations. This study is a legal-sociological study using a grounded research model to find evidence of the flexibility of Islamic law in determining the status of the law of the Ganjur tradition. The data required include the history of Ganjur, Ganjur practice, and people's views on Ganjur, which were explored through interviews with twenty informants and Focus Group Discussions (FGDs) with three traditional leaders, three religious leaders, and five traditional actors. To evaluate the data, the maqāṣid syarī'ah approach was utilized. The results indicate that the Ganjur tradition stems from the legend of Panji Laras and Panji Liris (male figures), who received a proposal from Andansari and Andanwangi (female figures). The act of proposing to a man (ngganjur) is considered a source of glory for a woman. Meanwhile, being proposed to by a woman (diganjur) denotes that a man is respected as a companion to his wife rather than dominated by her. The wedding ceremony is fully financed and organized by the woman's family. Following the event, the couple resides with the woman’s family for an indefinite period, until they have acquired sufficient resources to establish their own independent household. The husband and wife hold equal ownership of the family unit and collaboratively manage the household; the wife is not subordinate nor a complement to the husband (koncowingkeng). This study found that Islamic law’s flexibility could uphold the legitimacy of the Ganjur tradition with accurately proposed sharia.